Peranan Sektor Perikanan dan Kelautan Bagi Masyarakat dan Penerimaan Pajaknya Di Kota Sibolga - Ikhsan, Miftakhul; Dwiyanda, Muhamad Arshel; Hasan, Wahyu; Simangunsong, Yessica Cindy Erika (Syntax Idea, 2021)
Indonesia's marine natural resources potential is very abundant because two-thirds of Indonesia's territory is oceans. That is why the fisheries and marine sectors have a significant role in the Indonesian economy. One city that has great potential in the fisheries and marine sector is Sibolga. This study aims to: (1) analyze the role of the fisheries and marine sectors in achieving the Gross Regional Domestic Product (GRDP) of Sibolga; and (2) to analyze the role of the fisheries and marine sectors on tax revenues in Sibolga. In conducting this research, we use descriptive analysis method to explain the events that we find in the research process. The results of the analysis show that fisheries activities in Sibolga are superior and prospective. The productivity of the fisheries and marine sector in the city of Sibolga still shows fluctuating figures in the last 5 years. In addition, the fisheries and marine sectors also contribute to the PDRB of Sibolga City by contributing a large proportion and become a mainstay sector in the development and development of the city of Sibolga, as well as contributing to relatively volatile tax revenues.